SPSS for Starters and 2nd Levelers - Cleophas, Ton J.; Zwinderman, Aeilko H. (Springer, 2016)
This small book addresses different kinds of data files, as commonly encountered in clinical research and their data analysis on SPSS software. Some 15 years ago serious statistical analyses were conducted by specialist statisticians using mainframe computers. Nowadays, there is ready access to statistical computing using personal computers or laptops, and this practice has changed boundaries between basic statistical methods that can be conveniently carried out on a pocket calculator and more advanced statistical methods that can only be executed on a computer. Clinical researchers currently perform basic statistics without professional help from a statistician, including t-tests and chi-square tests. With the help of userfriendly software, the step from such basic tests to more complex tests has become smaller and more easy to take. It is our experience as masters’ and doctorate class teachers of the European College of Pharmaceutical Medicine (EC Socrates Project, Lyon, France) that students are eager to master adequate command of statistical software for that purpose. However, doing so, albeit easy, it still takes 20–50 steps from logging in to the final result, and all of these steps have to be learned in order for the procedures to be successful. The current book has been made intentionally small, avoiding theoretical discussions and highlighting technical details. This means that this book is unable to explain how certain steps were made and why certain conclusions were drawn. For that purpose additional study is required, and we recommend that the textbook “Statistics Applied to Clinical Trials,” Springer 2009, Dordrecht, Netherlands, by the same authors, be used for that purpose, because the current text is much complementary to the text of the textbook.